A Faith-Informed Model for Experiential Learning Applied to Faith Integrated Service-Learning. Issue 1 (24th December 2021) - Kaak, Paul; LaPorte, Michelle
Abstract: In this article, we propose that Christian college and university professors make use of experiential learning, particularly in the form of academic service-learning, in their academic courses. Accordingly, this proposal emphasizes faith-integrated service-learning, aiming for a distinctly Christian approach that goes beyond mere acts of Christian kindness. This article offers, therefore: (1) an argument for experiential learning in the context of faith-based learning, (2) a pedagogical model that resembles Jesus' own use of experiential learning with his disciples, (3) the application of this model to faith-based service-learning, and (4) the attendant recommendation that faith-based service-learning incorporate both relevant knowledge and wisdom from the Christian faith and faith-informed critical reflection. Practical suggestions and illustrations are offered for each phase of the model being proposed, as applied to an academic service-learning project in a Christian college course. This article presents the model that was introduced to the participants in the Faith Learning in Action (FLA) project that was the basis of the articles included in this Theme Issue of the Christian Higher Education journal. Christian educators, curriculum designers, and faculty developers who are compelled by a vision for more holistic Christian learning, across the disciplines and professions, will find some assistance here.